Existential and Possessive Constructions in English and German - Siranush Khandanyan (Armenian Folia Anglistika, 2010)
The article examines the semantic and syntactic characteristics of existential (es gibt / there is) and possessive (have / haben) constructions of English and German. The article underlines the effective methods of their teaching for those who study English as a foreign language. The research indicates that having a number of syntactic and semantic similarities, the aforementioned structures are distinguished with their unique forms of expression, which, in its turn, contributes to the elaboration of typology of the patterns.